Airborne remote sensing of Arctic boundary-layer mixed-phase clouds - Ehrlich, André; Bierwirth, Eike; Wendisch, Manfred (Universität Leipzig, 2010)
This article gives an overview on the investigations on Artic boundary-layer mixed-phase clouds conducted within the Arctic Study of Tropospheric Aerosol, Clouds and Radiation (ASTAR) in spring 2007. In particular the horizontal and vertical disribution of ice crystals within the clouds was determined by three independent airborne instruments (lidar, in situ and solar radiation measurements). Spectral measurements of cloud top reflectivity have been utilized to retrieve information on the ice phase by analyzing the spectral pattern of the cloud top reflectance in the wavelength range dominated by liquid water and ice absorption (1400-1700 nm). A new algorithm to derive an ice index which distinguishes pure ice, liquid water, and mixed-phase clouds was developed. The horizontal distribution of the ice index, observed during ASTAR 2007, agrees with airborne lidar and in situ measurements showing patches of glaciated clouds at an air mass transition zone within the investigated mixed-phase cloud fields. Information on the vertical distribution of ice crystals in mixed-phase clouds was derived by comparing the measured cloud top reflectivity in the wavelength band 1400-1700 nm to radiative transfer simulations. To interpret the data, the vertical weighting of the measurements was calculated. In the investigated wavelength range the weightings differ according to the spectral absorption of ice and liquid water. From the observed spectral cloud reflectivity with low values in the ice absorption maximum (1400 nm) and higher values at the liquid water absorption maximum (1700 nm) it was concluded that ice crystals were present in the otherwise liquid dominated cloud top layer. Although in situ measurements (limited due to vertical resolution and detection limits) did confirm these findings only in certain limits, the retrieved vertical structure is in agreement with published ground based remote sensing measurements.